Influence of Various Parameters on the Stability of a Paste Foamed - Ouslimani, N.; Mazouz, A.; Maalem, M.; Benferrah, N. (Asian Journal of Chemistry, 2013)
This study aims to investigate the influence of various parameters on the properties and quality of a foamed paste for printing with reactive dyes. The results show that the paste foamed has a lower viscosity than the paste usually because of the small amount of surfactant implementation which provides a better dyeing efficiency and water savings Thus, the fastness of fabrics printed with the paste foamed are the same as regular paste.